Analysis of the Critical Success Factors that Affect the Implementation of Local Agenda 21 in Thailand - Leknoi, Unruan (Journal of International Buddhist Studies, 2017)
Led by local governments and driven by the participation of local people, Local Agenda 21 (LA 21) has been implemented in Thailand to lay the foundation for sustainable management of natural and environmental resources. Unfortunately, after over a decade, only 2.39% of the local governments nationwide have taken the effort seriously. This article aimed to analyze the critical success factors that affect the implementation of LA 21 in Thailand using quantitative research. A questionnaire, developed according to the Stufflebeam’s CIPP model, was applied to systematically collect the data on the implementation of LA 21from every local government in Thailand that has implemented LA 21 to some degree (100%). The results were statistically analyzed by stepwise multiple regression. Three critical success factors in implementing LA 21 successfully in Thailand were found; namely the (1) number of private sectors joining the LA 21 operation team (NumPrivate), (2) implementation budget (ImpBudget) and (3) level of multilateral participation in implementation (ParImp). The relationship among the three factors fitted the equation , with a prediction reliability of 60.70 . The level of multilateral participation in implementation is the most critical factor in successfully implementing LA 21 in Thailand.